New Insights on Leptospira Infections in a Canine Population from North Sardinia, Italy: A Sero-Epidemiological Study - Ivana Piredda; Maria Nicoletta Ponti; Angela Piras; Bruna Palmas; Pierangela Pintore; Aureliana Pedditzi; Valentina Chisu (Biology, 2021)
Leptospirosis is a widespread zoonosis recognized as a re-emerging infectious disease in a wide variety of animal species, including humans and dogs. No data exist regarding the presence of Leptospira species in the canine population of Sardinia Island. This study reports the first sero-survey for leptospirosis in kennel and owned dogs from six areas of the north of Sardinia. Sera from 1296 dogs were tested by microscopic agglutination test (MAT) specific for nine different serovars that are known to be well widespread in the Mediterranean environment. Moreover, kidney homogenates from rodents collected from the study area were also analyzed by LipL32 real-time PCR and multi-locus sequence type (MLST) on the basis of the analysis of seven concatenated loci. A total of 13% of the examined sera (95%CI: 11–15) tested positive for one or more serovars of Leptospira MAT detected; antibodies for serogroup Icterohaemorrhagiae (57%; 95%CI: 49–65) were the most common, followed by serovars Bratislava (22%; 95%CI: 16–28), Canicola (14%; 95%CI: 9–19), and Grippotyphosa (7%; 95%CI: 3–11). MLST analyses on isolates from rodents identified L. interrogans and L. borgpetersenii genomospecies. Different serovars belonging to pathogenic Leptospira serogroups are circulating in dogs from the island. Moreover, data obtained from rodents, indicated that rodents likely act as reservoir of spirochetes. Further sero-epidemiological studies are needed in order to obtain data from other collection sites in Sardinia and to increase the information on Leptospira species circulating in this area.